Reading Rate and Comprehension for Text Presented on Tablet and Paper: Evidence from Arabic - Hermena, Ehab W.; Sheen, Mercedes; AlJassmi, Maryam; AlFalasi, Khulood; AlMatroushi, Maha; Jordan, Timothy R. (Frontiers in Psychology, 2017)
The effectiveness of tablet computers to supplement or replace paper-based text in everyday life has yet to be fully revealed. Previous investigations comparing reading performance using tablets and paper have, however, reported inconsistent results. Furthermore, the interpretability of some previous findings is limited by lack of experimental control over variables like text display conditions. In the current study, we investigated reading performance for text presented on tablet and paper. Crucially, the levels of luminance and contrast were matched precisely across tablet and paper. The study used Arabic text which differs substantially from the languages used previously to investigate effects of tablet and paper on reading, thus offering a distinctive test of the influence of these two media on reading performance. The results suggest that when text display conditions are well-matched, there is no reliable difference in reading performance between the two media. Also, neither the order of medium (reading from tablet or paper first), nor familiarity with using a tablet significantly influence reading performance. These results call into question previous suggestions that reading from tablets is linked to poorer reading performance, and demonstrate the benefits of controlling text display conditions. These findings are of interest to reading scientists and educators.